ANALISA DAN PERANCANGAN APLIKASI CAREER DEVELOPMENT CENTER PADA STMIK INSAN PEMBANGUNAN (STUDI KASUS : PROGRAM STUDI INFORMASI) - Vanessa Stefany; . Nurasiah; Gusti Nyoman Budiadnyana (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2017)
Vanessa Stefanny1,Nurasiah, S.Kom.,MMSI2, Gusti Nyoman Budiadnyana, S.Kom., MM2Jurusan Sistem Informasi, STMIK Insan Pembangunan1MahasiswaJurusanSistemInformasi, STMIK Insan Pembangunan2Dosen Pengajar, STMIK Insan PembangunanJl. Raya Serang Km. 10 Bitung – TangerangABSTRACTIn order to facility data of ex-graduate maintaining and career information distributionto all of member of STMIK Insan Pembangunan especially Information System,information system is made to handle that. It is an application that named CareerDevelopment Center. In processing that aplication, the writer do examination byinterview, observation and from books or literatures and then continue to model it withUML diagrams. Along with this system, it is hoped that recapitulaton of ex-graduateand career information spreading about job vacancy, tips and training/workshop canhelp user to maintain it.Key Words : UML, Career, ex-graduate, STMIK Insan Pembangunan, Analisys